Relationship between manual air valve positioning, water quality and energy usage in activated sludge processes. (15th April 2020) - Reifsnyder, Samuel; Garrido-Baserba, Manel; Cecconi, Francesca; Wong, Larry; Ackman, Phil; Melitas, Nikos; Rosso, Diego
Abstract: Diffused aeration is the most implemented method for oxygen transfer in municipal activated sludge systems and governs the economics of the entire treatment process. Empirical observations are typically used to regulate airflow distribution through the adjustment of manual valves. However, due to the associated degrees of freedom, the identification of a combination of manual valves that optimizes all performance criteria is a complex task. For the first time a multi-criteria optimization algorithm was used to minimize effluent constituents and energy use by parametrizing manual valves positions. Data from a full-scale facility in conjunction with specific model assumptions were used to develop a base-case facility consisting of a detailed air supply model, a bio-kinetic model and a clarification model. Compared to the base-case condition, trade-offs analysis showed potential energy savings of up to 13.6% and improvement of effluent quality for NH4 + (up to 68.5%) and NOx (up to 81.6%). Based on two different tariff structures of a local power utility, maximum costs savings of 12800 USD mo −1 to 19000 USD mo −1 were estimated compared to baseline condition. Graphical abstract: Image 1 Highlights: Multi-objective optimization to minimize energy use by parametrizing manual valves positions. Development of an advanced dynamic model of the air distribution system. Trade-offs analysis showed potential energy savings of up to 13.6%. Improvement of effluent quality for ammonium (up to 68.5%) and nitrite + nitrate (up to 81.6%). Accurate estimations from changes in the tariff structures of the power utilities.